El procedimiento inspectivo y la protección frente al trabajo infantil Loreto 2015-2019 - Hidalgo Piña, Elena Margarita (2022)
The objective of this research is based on child labor, in direct relation to the application of the inspection procedure, and the protocol that is applied for its proper execution, during the years 2015-2019, in the department of Loreto. We have opted for an investigation with a qualitative approach, which allows us to point out the tools that are executed for a proper application of the inspection procedure; and similarly, establish solutions to infractions in the matter of child labor. For this reason, a non-experimental, evolutionary and dogmatic legal methodology was applied and executed, using instruments such as data collection, interviews and information gathering. So, the analysis of the information based on child labor and the inspection procedure, of our interviewed population is related to the result of the questionnaire made to ten (10) professionals who know about the subject, made up of lawyers, administrators and economists, in order to carry out an interpretive and content analysis task, taking into account that it is focused on the department of Loreto; Therefore, truthful information has also been extracted on the cases of child labor found during the years 2015 - 2019, information provided by the Loreto Regional Administration of the National Superintendence of Labor Inspection - SUNAFIL and the Regional Directorate of Labor and Employment Promotion of Loreto – DRTPE-L.